HAMBATAN PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI DI PUSKESMAS DARUSALLAM KOTA MEDAN (POTRET KOMUNITAS) - Mey Elisa Safitri; Hafsah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Exclusive breastfeeding during the first six months of life has been proven to significantly reduce infant morbidity and mortality while contributing to the improvement of human resource quality. However, the coverage of exclusive breastfeeding in Indonesia, including Medan City, remains below the national target. This study aimed to identify barriers to exclusive breastfeeding among breastfeeding mothers at Darusallam Public Health Center, Medan. A quantitative descriptive survey design was applied, involving 140 mothers with infants aged 0–6 months. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis included univariate, bivariate (chi-square test), and multivariate (multiple logistic regression). The results showed that only 39.29% of respondents practiced exclusive breastfeeding, while 60.71% did not. The main barriers identified were lack of maternal knowledge (35.0%), employment factors (32.1%), and low family support (18.6%). Bivariate analysis revealed significant associations between maternal education, employment status, family support, and knowledge with exclusive breastfeeding practice (p<0.05). Multivariate analysis demonstrated that maternal knowledge was the most dominant factor with OR=8.17 (p=0.001), followed by family support (OR=5.93), education (OR=3.38), while maternal employment was found to be a barrier (OR=0.23). It can be concluded that maternal knowledge is the most dominant barrier to exclusive breastfeeding practice, along with family support and employment. Therefore, public health interventions should focus on improving maternal knowledge through education and lactation counseling, strengthening family support, and implementing mother-friendly workplace policies that provide adequate lactation facilities.